2022
DOI: 10.1111/jocs.16699
|View full text |Cite
|
Sign up to set email alerts
|

Total anomalous pulmonary venous connection: 16 years of surgical results in a single center

Abstract: Purpose: The aim of the study was to analyze the surgical outcome of patients with total anomalous pulmonary venous connection (TAPVC) who underwent cardiac surgery.Methods: A retrospective study was carried out. Patients with diagnosis of TAPVC undergoing cardiac surgery at the National Institute of Cardiology Ignacio Chávez, from January 1, 2003 and June 30, 2019 were included. Descriptive statistics were calculated, as well as a bivariate analysis of the variables associated with mortality.A logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Complex congenital heart defects, such as TAPVC combined with single ventricle physiology, requires innovation and dedication for successful therapy and treatment 7 . The promising result of the study reported by Cervantes‐Salazar et al 1 gives our field hope for a better future for these patients.…”
Section: Invited Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…Complex congenital heart defects, such as TAPVC combined with single ventricle physiology, requires innovation and dedication for successful therapy and treatment 7 . The promising result of the study reported by Cervantes‐Salazar et al 1 gives our field hope for a better future for these patients.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Cervantes-Salazar et al 1 report the long-term surgical outcomes of 414 patients with total anomalous pulmonary venous connection (TAPVC) who underwent cardiac surgery at one institution from TAPVC comprises 1.5% of congenital heart disease, and necessitates emergent surgical repair in the neonatal or infantile period, immediately after confirmation with echocardiography. 2 Mortality is virtually 100% for those having PVO and being left surgically untreated by 4 months of age.…”
Section: Invited Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Neonates with the total anomalous pulmonary venous return (TAPVR) with an obstruction to the pulmonary venous return should have immediate surgical correction [ 26 , 27 , 28 , 29 ]. It should be noted that some newborn infants with markedly reduced pulmonary blood flow may manifest TAPVR only after performing BT shunting.…”
Section: Management Of Cardiac Malpositionmentioning
confidence: 99%